Influence Of Drugs On The Fertility Of Ural Glycoryza (Glycyrrhiza Uralenses) - N.D. Tadjetdinov; A.K.Saparova; G.I. Saparniyazov (Zien Journals, 2024)
In the saline lands of Karakalpakstan, special attention should be paid to measures for washing the soil during sowing, and planting by treating licorice seeds with a stimulant "fitovak" gave a good result. So, in the field, with good soil washing and sowing of licorice seeds of the Ural, soaked for 36 hours with 30 ml of the stimulant "fitovak" per 10 liters of water, the germination of the seeds showed high positive indicators compared with other drugs.
Keywords: Ural licorice; licorice biostimulator; phytovac